The Criminalization of Siti Aisyah Case: The Suspect in the Murder of Kim Jong Nam (Legal and Justice Approach) - Shiddiqii, Mathlangish; Utama, Rafly Febrian (Faculty of Law, Universitas Negeri Semarang, 2023)
This article will analyze the role of the victim in the murder based on the true story of a migrant worker named Siti Aisyah, a domestic worker in Malaysia. This article will explain the unequal position of domestic workers in relation to employers, gender inequality, victim status, minority status and so on, even victim analysis is a problem today. Because this article really needs to be discussed with the key TKW working abroad to know that their situation is really very vulnerable with various inherent aspects. Moreover, cases like this are not new, we hear that there are many helpless victims who are forced or used to help criminals. Moreover, cases like this are not new, we hear that there are many helpless victims who are forced or used to help criminals. Therefore, we hope that this article can help broaden our views and thoughts, especially for TKI who want to work abroad in the country, who are aware of the law and must also be aware of the law, add insight and last but not least, improve self-awareness. . Therefore, we hope that this article can help broaden our views and thoughts, especially for TKI who want to work abroad in the country, who are aware of the law and must also be aware of the law, add insight and last but not least, improve self-awareness.